The Perspective on The Norm of Severance Pay Compensation For Fixed-Term Employment Contracts Based on Law No. 11 of 2020 on Job Creation is Linked to Legal Certainty - Nursa’adah; Dauman (Yayasan Sinergi Kawula Muda, 2023)
The changing landscape of the millennial-era business world demands affordability and quality, necessitating a minimal cost strategy for optimal performance. Before 2000, permanent employment was the norm, but thereafter, employers began using fixed-term employment agreements managed by outsourcing firms. Various aspects of the employer-employee relationship have been regulated in employment law, including Law No. 13 of 2003 on Manpower and Law No. 11 of 2020 on Job Creation. However, implementing these regulations, particularly concerning compensation for fixed-term employment under Law No. 11 of 2020, has created legal challenges, notably for employers in sectors like cleaning, parking, security, and more. This study employs a normative legal research approach, analyzing legal provisions and their real-world applications. It aims to assess the applicability of severance compensation rules for fixed-term employment agreements in outsourcing companies. The findings will be presented in a report scheduled for publication in July 2023.